ROCKET LOAD TEST BASED ON INERTIAL MEASUREMENT UNIT SENSOR IN SUPPORTING NATIONAL AIR DEFENSE - Mudarris Mudarris; Muhammad Romario Basirung; Iris Sumariyanto (The Republic of Indonesia Defense University, 2022)
The development of rocketry and rocket payload technology is very rapid in the industrial era 4.0. Rockets are usually used as dynamic sensors or carriers for specific missions for sensing and retrieving data from space for meteorological, military, etc. This article aims to design, realize and test a Rocket Payload Monitoring System Based on an Inertial Measurement Unit (IMU) Sensor to monitor the condition of the payload movement behavior. Rocket Payload is a substance carried in a Payload Test Rocket (RUM) in the form of a cylindrical payload. This research focuses on designing a Graphical User Interface (GUI) application to display data in real-time. The type of research used is Research and Development (R&D) with a prototyping development model. The results obtained in the form of Rocket Payload Design and GUI design can be concluded that the GUI application can visualize all sensor and camera data in real-time.